Preparation and characterizaton of maize stalk fiber/calcium carbonate/polylactic acid hybrid biocomposites for advanced applications - Magunga, Lwazi Glen (Central University of Technology, 2023)
Maize holds a crucial position as a vital food crop, playing a significant role in both the economy and food security of South Africa. Given its status as a stable food, the production of maize is notably high, resulting in a substantial amount of maize stalk waste. Effectively addressing this waste has become a pressing concern, sparking the development of various solutions. One particularly promising approach involves the integration of maize stalk waste with polymers to bolster the mechanical properties of polymers. Among the plethora of polymers available, PLA stands out as one of the most widely utilized polymers, renowned for its biodegradability, and low toxicity. Its inherent limitations however include: restricted heat resistance, brittleness, and susceptibility to moisture absorption, and thereby present an opportune scenario for reinforcement to enhance its overall properties. This study investigates the potential of using maize stalk fiber (MSF) and Calcium carbonate (CaCO3) as a reinforcing filler in a PLA matrix. The properties of interest in this study were morphology, flammability properties, dynamic mechanical analysis, rheological properties, and thermal stability. 5%, 10%, 15% and 20% of the fiber dosages were incorporated into the in the PLA matrix. Higher filler dosages (i.e 20%) resulted in high fiber pullouts in the PLA matrix. The incorporation of CaCO3 further improved dispersion and enhanced fiber-polymer interactions. Incorporation of 20% MSF increased the peak heat release rate (pHRR) of PLA from 554.5 kW/m2 to 697.4 kW/m2 whilst the incorporation of calcium carbonate reduced the pHRR to 483.3 kW/m2. Increasing CaCO3 dosage improved the thermal stability of PLA. Higher storage modulus was observed for hybrid composites containing 15 and 20% MSF. The results of the study showed that the CaCO3 and MSF fillers have the potential to be used as reinforcing agents in PLA biocomposites for various applications.
Master of Health Sciences in Environmental Health
Keywords: Maize stalk; polylactic acid; calcium carbonate; flammability properties; degradation